Anais Do XX Congresso Brasileiro De Engenharia Química 2015
DOI: 10.5151/chemeng-cobeq2014-1938-16781-145061
|View full text |Cite
|
Sign up to set email alerts
|

Extração Supercrítica Com Utilização De Modificadores E Caracterização a Partir Da Semente De Cumaru (Dipteryx Odorata)

Abstract: RESUMO -Este trabalho tem como objetivo a extração e quantificação de compostos bioativos da semente do cumaru por meio de extração convencional (soxhlet) e supercrítica utilizando dióxido de carbono e solventes modificadores. As extrações supercríticas foram realizadas numa faixa de pressão de 180 -220 bar e temperatura de 60 -80ºC. O planejamento experimental foi definido a partir do design fatorial fracionado (método Taguchi). Os extratos foram analisados por cromatografia liquida (HPLC) e gasosa com espect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
2
0
0
Order By: Relevance
“…Regarding the yield results, data similar to those obtained in this study for cumaru seeds were found when comparing conventional and supercritical ethanolic extractions of bioactives, resulting in a yield of 46.5%, using Soxhlet apparatus [23]. The high yield values obtained by the Soxhlet extraction method were attributed to solvent recirculation and solute-solvent interactions [24].…”
Section: Discussionsupporting
confidence: 83%
“…Regarding the yield results, data similar to those obtained in this study for cumaru seeds were found when comparing conventional and supercritical ethanolic extractions of bioactives, resulting in a yield of 46.5%, using Soxhlet apparatus [23]. The high yield values obtained by the Soxhlet extraction method were attributed to solvent recirculation and solute-solvent interactions [24].…”
Section: Discussionsupporting
confidence: 83%
“…Extractions of leaves, branches, residues (separated into epicarp + mesocarp, and endocarp) and seeds of Dipteryx odorata and Dipteryx punctata have also been performed in a Soxhlet apparatus and, as in this study, the highest yields were obtained for extracts of fruit residues (epicarp + mesocarp) (44.1% and 54.2%) and for the seeds (48.9% and 44.5%) of the two species, respectively [10]. The yield of Dipteryx odorata seed extractions also resulted in values as high as 46.5% [34].…”
Section: Discussionsupporting
confidence: 54%